ANALYSIS OF THE INFLUENCE OF CUSTOMER TRUST ON CUSTOMER LOYALTY THROUGH REPURCHASE INTENTION MEDIATION (TOKOPEDIA CASE STUDY) - Ade Line Swastika; Muchsin Saggaff Shihab (Jurnal Scientia, 2023)
The hack that was experienced by Tokopedia in early February 2020 was that around 91 million user data and more than 7 million merchants data were stolen by a groups of hackers. Reportedly, the data was sold for US$ 5,000 or Rp. 74.5 million at an exchange rate of Rp. 14,900/US$. The data taken included user names, e-mails, and passwords to see if the decline in Tokopedia's visitors growth was significantly affected by the decline in consumer trust due to the data leak in May 2020. This study also wants to examine further whether this will affect consumer loyalty in the long term . The results show that in 2019, 81% of consumers said they should first trust a brand before purchasing. That is, consumers are willing to reward businesses when the product is successful in building consumer trust